Influence of Irrigation and Fertigation Levels through Intermittent Drip Irrigation on Yield Contributing Parameters of Carrot (Daucus carota L.) - RAWAT, GOVIND; JENA, SUSANTA KUMAR; UTTAM S. KADAM; PRAVIN M. INGLE (Journal of the Indian Society of Coastal Agricultural Research, 2026)
Water and nutrient management are important for sustainable development of agriculture, so as to achieve higher production. This experimental study aimed to determine the influence of pulse irrigation and fertigation levels through drip irrigation on yield contributing parameters of carrot (Daucus carota L.), which were conducted during 2019-20 and 2020-2021 in Dapoli (17° 45’ 14’’ N and 73° 10’ 45’’E), coastal Ratnagiri, Maharashtra. Three irrigation water levels of 80, 100 and 120% of crop evapotranspiration (ETc) were applied through four number of pulses P1, P2, P3 and P4 with constant 30 minutes interval between each pulse. The recommended nutrients were applied with water-soluble fertilizer with rates 80, 100 and 120% of recommended dose of fertilizer (RDF) along-with irrigation water through drip. The highest shoulder diameter was found in P4 pulse number, I2 (1.0 ETc) irrigation level and F2 (1.0 RDF) fertigation level; and carrot root length in P2 pulse number, I3 (1.2 ETc) irrigation level and F3 (1.2 RDF) nutrient level. The largest carrot diameter was observed in treatments of P4I2, P4F2, F3I2 and P4I2F2, and treatment combinations P41I41, P4F3, F1I1 and P2I3F3 recorded longest carrot roots. The maximum yield of 40.64 t ha-1 and water productivity of 1.37 t ha-1 cm-1 was obtained from P4I2F2 and P4I1F1, respectively.